A critical assessment of the challenges facing heads of department in colleges of education in South East Nigeria - Victoria, Ezeneme Ebele (Kuras Institute, 2025)
Purpose − The role of Heads of Department (HODs) in Colleges of Education is important to the efficient administration and smooth functioning of academic programs. In South East Nigeria, specifically in Anambra and Imo States, HODs face a myriad of challenges that hinder their ability to provide effective leadership and ensure optimal outcomes for students and staff. This study critically assesses the challenges faced by Heads of Department (HODs). The research investigates key factors affecting departmental administration, including inadequate funding, lack of regular supervision, lack of motivation among lecturers, and indiscipline among both students and staff. Method − This study used a descriptive survey design and was conducted in Colleges of Education in Anambra and Imo States. The population consisted of 600 respondents, including lecturers and students from the selected colleges. Data were collected using a validated 4-point Likert scale questionnaire, titled A Critical Assessment of the Challenges Facing Heads of Department in Colleges of Education in South East Nigeria. Cronbach’s Alpha reliability test yielded an index of 0.88. Descriptive statistics, including frequencies and percentages, and inferential statistics like ANOVA and bootstrapping were employed to analyze the data, revealing significant differences and key patterns in departmental administration. Findings − The study found that inadequate funding severely limits the availability of teaching resources, staff training opportunities, and the implementation of innovative programs. Poor supervision and lack of motivation were found to negatively impact staff productivity, academic quality, and departmental harmony. Indiscipline among both lecturers and students further exacerbates administrative challenges, leading to conflicts and a decline in institutional credibility. The study concludes that addressing these challenges requires a multifaceted approach, including increased funding, regular supervision, staff motivation, and promoting discipline within departments. The findings of this study offer actionable plan for educational policymakers and administrators seeking to improve the administration and leadership effectiveness in Colleges of Education in South East Nigeria. Recommendations are provided for strategic interventions to enhance departmental operations and ensure the overall success of these institutions.